2018
DOI: 10.1158/1535-7163.mct-17-0302
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-Resistant HER2+ Breast Cancer Cells Retain Sensitivity to Poly (ADP-Ribose) Polymerase (PARP) Inhibition

Abstract: HER2-targeted therapies, such as trastuzumab, have increased the survival rates of HER2 breast cancer patients. However, despite these therapies, many tumors eventually develop resistance to these therapies. Our lab previously reported an unexpected sensitivity of HER2 breast cancer cells to poly (ADP-ribose) polymerase inhibitors (PARPi), agents that target homologous recombination (HR)-deficient tumors, independent of a DNA repair deficiency. In this study, we investigated whether HER2 trastuzumab-resistant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
(57 reference statements)
4
13
0
Order By: Relevance
“…Acquired resistance to lapatinib has been shown to be heterogeneous in nature and involves a myriad of pathways and can vary across cell lines [31,36]. Supporting our observations, veliparib, another PARP inhibitor, was reported to induce apoptosis in a three cell line models of trastuzumab resistance [45]. Our results provide evidence to support the continued research into the effects of single-agent PARPi or in combination with HER2 targeted therapies for the treatment of HER2 positive breast cancers with acquired resistance to HER2-targeted therapies.…”
Section: Discussionsupporting
confidence: 83%
“…Acquired resistance to lapatinib has been shown to be heterogeneous in nature and involves a myriad of pathways and can vary across cell lines [31,36]. Supporting our observations, veliparib, another PARP inhibitor, was reported to induce apoptosis in a three cell line models of trastuzumab resistance [45]. Our results provide evidence to support the continued research into the effects of single-agent PARPi or in combination with HER2 targeted therapies for the treatment of HER2 positive breast cancers with acquired resistance to HER2-targeted therapies.…”
Section: Discussionsupporting
confidence: 83%
“…However, PARPs, as well as macro‐PARP family members, were closely related with NF‐κB signaling in human diseases. For instance, PARPi (PARP inhibitors) induced cytotoxicity in HER2 + breast cancer cells through inhibition of NF‐κB signaling and reduced p65 binding at the IL8 promoter . Kwon et al reported that the PARP inhibitors (olaparib) could overcome cisplatin resistance of head and neck cancer cells via PAR‐p53‐NF‐κB interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PARPi (PARP inhibitors) induced cytotoxicity in HER2 + breast cancer cells through inhibition of NF-κB signaling and reduced p65 binding at the IL8 promoter. 26 Hunter et al 28 revealed that PARP-1 was differentially required in the induction of NF-κB, and radiosensitization by PARP-1 inhibition was exclusively due to the inhibition of NF-κB. PARP10, also a member of mono-ADP ribosyltransferase, repressed the activation of NF-κB signaling and downstream target proteins based on catalytic activity and polyubiquitin binding of PARP10.…”
Section: Discussionmentioning
confidence: 99%
“…19). Samples were processed for analysis using the PanCancer Pathways Plus panel as per the manufacturer's (7,17). The nSolver 4.0 program was used in data analysis.…”
Section: Rna Isolation and Nanostring Pancancer Pathways Analysismentioning
confidence: 99%